Settlement Of Civil Disputes Regarding Incompatibility Of Objects Of Online Purchase - Hadziqotun Nadliyah; Dhevi Nayasari (Universitas Islam Lamongan, 2021)
The thing to remember is that buying and selling online is on the principle is the same as the factual sale and purchase on generally. Consumer protection law related to sale transactions even buying online as we previously explained is no different with the applicable law in real buying and selling transactions. The difference is only in the use of internet facilities or means other telecommunications. The result is in buying and selling transactions online it is difficult to do execution or real action if there is a dispute or a criminal act of fraud. Deep cyber nature transactions electronically allows everyone either the seller not the buyer disguises or falsifies the identity inside every transaction or sale and purchase agreement. In the event that the business actor or seller is using an identity fake or gimmick in buying and selling online, then business actors can also be convicted based on Article 378 of the Book The Criminal Code (“KUHP”) on fraud and Article 28 paragraph (1) of the ITE Law on spreading fake news and misleading which results in consumer losses in Electronic Transactions.